Tindak Tutur Ilokusi dalam Anime Kimetsu No Yaiba (Gotouge, 2019) - Putri, Desy Amalia; Martawijaya, Asteria Permata (Sekolah Tinggi Bahasa Asing Yapari-ABA, 2023)
This study examines the illocutionary speech acts in Kimetsu no Yaiba, an anime by Koyoharu Gotouge in 2019. The purpose of this study is to describe the types of illocutionary speech acts used in conversations in the Kimetsu no Yaiba, and to examine the politeness strategies used in conversations in this anime. The method used is the descriptive research method. The data collection used listening and note-taking techniques. The data review technique used is contextual. Based on the analysis, it is found that from 40 data, there are assertive speech acts (8), directive speech acts (22), commissive speech acts (4), expressive speech acts (3) and declarative speech acts (3). The strategies used in the Kimetsu no Yaiba are bald on record (19) used by speakers who are not familiar with speech partners, and speakers who are familiar with speech partners, positive politeness (19) used by speakers who are familiar with speech partners and negative politeness (2) used by speakers who are not familiar with speech partners.